Exploring the connection between ego-resiliency and health behaviors: a cross-sectional study of Polish health sciences students - Małgorzata Dębska-Janus; Paweł Dębski; Agnieszka Nawrocka; Jacek Polechoński; Wojciech Madejczyk; Karina Badura-Brzoza (BMC Psychiatry, 2024)
Abstract Background The aim of this study was to examine the relationship between ego-resiliency and the intensity of health behaviors among Polish health sciences students. Methods The study involved 483 students from health-related faculties in southern Poland, consisting of 314 women (63.7%) and 179 men (36.3%). The average age of the participants was 21.7 ± 2.5 years. To assess resiliency (ER), the Ego-Resiliency Scale (ER89-R12) by Block and Kremen was used in its Polish adaptation. The intensity of health behaviors was examined using the Health Behavior Inventory (HBI) developed by Z. Juczyński. Results The results revealed a positive correlation between the intensity of health behaviors and ER (r = 0.43, p < 0.001), both for the general factor and its categories (positive mental attitude, proper eating habits, preventive actions, and prohealth activities). Students with a high level of health behaviors exhibited significantly higher ER (M = 38.95, SD = 5.15) compared to those with average (M = 35.93, SD = 5.03) and low (M = 32.97, SD = 5.12) HBI levels. Among the HBI categories, Positive Mental Attitude showed the strongest correlation with both general ER and its factors: optimal regulation (OR) and openness to life experiences (OL). Furthermore, the correlation was found to be stronger with the OR and weaker with OL. Conclusion Higher ER in students is correlated with a greater frequency of health behaviors. Nurturing the development of ER may contribute to the maintenance of prohealth practices despite life difficulties and temporary loss of motivation. This, in turn, promotes the regularity of health behaviors, which is crucial for their positive impact on overall health.